Man as a Normative Creature - Peregrin, Jaroslav (Teorie vědy / Theory of Science, 2012)
The human differs from other animal species in a lot of ways, among the most important of which are reason, language, and also the ability to follow rules. In this text I argue that it is especially the last ability which is crucial and without which the others would be inconceivable. We, humans, are social beings not only in the sense that we live in societies, but also in that these societies are structured by complex webs of rules, which determine, in an essential way, the modus vivendi of the people who constitute them, and, as a consequence, determine human as such. A system of rules can create a kind of "inner space" - we can accept them and thus enter the space, or we can just merely register them, as it were, "from the outside". The dialectics of these two positions lets us see that though the normative dimension is quite crucial for human as a social being and though it is hardly capturable by the common scientific methods of "disengaged observation", the normative dimension is nothing esoteric, which would be dubious from the viewpoint of science.